Implementation of The Tahfidz Quran Program in Increasing Religiosity at SMP Muhammadiyah 57 Medan - Tsania, Ulfa; Fanreza, Robie (SAINTIS Publishing, 2025)
This study is to determine the implementation of the Quran tahfidz program which has been carried out in accordance with the program at SMP 57 Muhammadiyah, Mustafa, Medan. The research data collection technique uses qualitative methods with technical observation, interviews and documentation. Analysis uses library research using literature in the form of books and is also in accordance with the results of the report notes in the research. In this research, a problem was found, namely that the implementation of the tahfidz program was less effective due to inadequate tahfidz hours, so that memorization was not done regularly. However, the results of the research show that the implementation of the tahfidz program at SMP 57 Muhammadiyah can increase students' religiosity well because it fosters awareness that a hafidz's soul must be good and also has an influence on students' religiosity which can be seen from the results of changes in the development of character and morals in students. So, with the implementation of the tahfidz Quran activity, it will grow and increase awareness in the human spirit of the importance of this tahfidz program in schools with the Koran, and the tahfidz activity can be a movement for evil and good deeds. In implementing tahfidz activities, targets and methods for memorizing are also needed, such as the importance of good focus in memorizing, etc., which will be studied as problematic in this research.